Regional Disparities and Transfer Policies in Russia : Theory and Evidence - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2001)
In this paper we examine economic disparities across regions in Russia and offer a theoretical treatment of various transfer rules between different regions. We analyze the principle of partial equalization, which implies that the more depressed regions should be subsidized by the more advantaged regions, but, the burden on more prosperous regions should not be excessive. Although, contrary to the partial equalization principle, the gaps between the richer and poorer regions have widened since the transition, there are some signs that this trend could be reversed.